2007
DOI: 10.1002/prot.21587
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of transition metal‐binding sites from apo protein structures

Abstract: Metal ions are crucial for protein function. They participate in enzyme catalysis, play regulatory roles, and help maintain protein structure. Current tools for predicting metal-protein interactions are based on proteins crystallized with their metal ions present (holo forms). However, a majority of resolved structures are free of metal ions (apo forms). Moreover, metal binding is a dynamic process, often involving conformational rearrangement of the binding pocket. Thus, effective predictions need to be based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 49 publications
6
127
0
Order By: Relevance
“…Metal ion binding sites were predicted using MetSite, 39 CHED, 40 and FEATURE 41 servers and by the ZincFinder program. 43 Additional protein family classification was performed with the SVM-Prot server.…”
Section: Prediction Of Metal Ion Binding Sitesmentioning
confidence: 99%
“…Metal ion binding sites were predicted using MetSite, 39 CHED, 40 and FEATURE 41 servers and by the ZincFinder program. 43 Additional protein family classification was performed with the SVM-Prot server.…”
Section: Prediction Of Metal Ion Binding Sitesmentioning
confidence: 99%
“…There have been several prediction methods based on structural information, such as the threading model (Sodhi et al 2004;Goyal et al 2008) and the force field model (Schymkowitz et al 2005). An empirical method based on the comparison of holo-apo pairs of known metal-binding sites appears to be one of the most practical approaches currently available because of the quality of the results (Babor et al 2008). An ambitious de novo approach based on a sequence using a machine-learning method has also been developed (Lippi et al 2008), although its prediction ability appears to be limited compared with the structure based predictions .…”
Section: Search By Amino Acid Sequencementioning
confidence: 99%
“…It has been observed that many metal binding sites in proteins are centered in a shell of hydrophilic ligands surrounded by a hydrophobic area. 6 A number of algorithms are available for predicting metal binding sites [6][7][8][9][10][11][12] and metal binding proteins. 13 Mostly, they are based on information derived from holo forms.…”
Section: Introductionmentioning
confidence: 99%